Pengembangan Perangkat Pembelajaran Pendidikan Jasmani Adaptif Permainan Bocce Berbasis PBL Bagi Down Syndrome Untuk Mengajarkan Keterampilan Motorik Dan Berinteraksi Sosial - Birriy, Ahmad Fawaid; Indahwati, Nanik; Nurhasan, Nurhasan (Journal of Sport Science and Education, 2020)
This research aims to develop a learning material for adaptive physical education with Problem-Based-Learning model applied to down syndrome students in the school for special need to teach motor capability and sosial interactiion. This Research and Development will use the ADDIE methods in applying learning tools through two phases. The small trial scale held in one school (3 students), and the large trial scale held in two schools (15 students). Results of smallscale trial: from the learning process gotÂ  83,3 % (very good), response from user got 88 %, result of social interaction skills form and motor skills form got 94 % and 92 % (very good). Results from large scale trial: average from the learning process got 89% (very good), average from users respon got 80,5 %, average value of social interaction skills form and motor skills form got 97,5 % and 96,8 % (very good). Based on the results, it concluded that the developed learning tools was already feasible for the down syndrome and it can be employed to teach motor skills and interact socially, and make a positive response from teachers. Hopefully that the product can be useful in the world of education, especially for DS.